What is the utility of urodynamics, including ambulatory, and 24h monitoring, in predicting upper urinary tract damage in neuro-urological patients and other lower urinary tract dysfunction? ICI-RS 2017 - (:unkn) unknown (WILEY, 2018)
AimsThis article focuses on how, and if, urodynamics can help to identify which kidneys are in danger of deteriorating in function and also gives recommendations for future research. MethodsAt the International Consultation on Incontinence-Research Society (ICI-RS) in 2017, a multidisciplinary group presented a literature search of what is known about the utility of Urodynamics, including ambulatory, and 24h monitoring, in predicting upper urinary tract damage in neuro-urological patients and other lower urinary tract dysfunctions. Wider discussions regarding knowledge gaps, and ideas for future research ensued and are presented in this paper along with a review of the evidence. ResultsThe current treatment strategy both in congenital and acquired neurogenic bladder is rather aggressive and successful when addressing hazards to kidney function. This article has highlighted uncertainties concerning the use of 40 cmH2O DLPP and even the lower value of 20. The current literature suggests that patients with spina bifida and those with spinal cord injury have a higher risk of developing upper urinary tract damage and kidney function impairment than those with multiple sclerosis. ConclusionsFuture research should focus on less invasive methods to assess the risk to the upper and lower urinary tract such as urine and serum measurements of cytokines that are involved in the pathophysiology of urinary tract impairment.
Keywords: renal function; upper urinary tract; urodynamics; INTERNATIONAL CONTINENCE SOCIETY; DETRUSOR SPHINCTER DYSSYNERGIA; STANDARDIZATION SUB-COMMITTEE; SPINAL-CORD-INJURY; CYSTATIN-C; BLADDER DYSFUNCTION; RENAL-FUNCTION; NEUROLOGICAL PATIENT; SERUM CREATININE; WALL THICKNESS